Training on Writing Personal Statement for Affirmation Scholarship of Educational Fund Management Institution - Peggy M. Jonathans; Jusuf Blegur; Anggreini D. N. Rupidara; Maryana M. Atambaru (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2022)
Preparing a personal statement for the LPDP scholarship is practical, but it has proven to be one factor that makes numerous applicants drop out during the first stage of selection. This polemic is motivated by applicants who have not been critical and credible in constructing a statement according to the sponsor's criteria. Applicants often prepare personal statements according to their respective “ambitions”. Whereas every scholarship competition, sponsors need applicants who can answer the sponsor’s agenda, both short-term, medium-term, and long-term. To bridge the polemic, preparing a personal statement based on the seminar, training, clinical, and evaluation methods for the participants was tricked out. There were eight participants involved, including teachers (50%), lecturers (12,5%), education staff (12,5%), and final semester students (25%). The mentoring results succeeded in helping participants have an LPDP scholarship account (100%), and the average assessment of the draft personal statement of the participants met the criteria for the trial activity (3,04). Despite having a good personal statement structure, participants conducted longitudinal peer reviews and improvements to several indicators that had low average values. Including less-than-delightful experiences (2,88), what was the last thing you taught yourself? (3), as well as mention and explain 1 (one) thing that distinguishes you from other participants (2,75).